Unraveling the Hidden Diversity of the Native White Claw Crayfish in the Iberian Peninsula - Martín-Torrijos, Laura; Buckley, David; Doadrio, Ignacio; Machordom, Annie; Diéguez-Uribeondo, Javier (Frontiers in Ecology and Evolution, 2021)
Several European freshwater crayfish species are currently included in one of the IUCN Red list categories. In the Iberian Peninsula, the native Austropotamobius pallipes species complex (the white clawed crayfish, WCC) has experienced a drastic decline since 1973. Implementing conservation management strategies for this species requires a better understanding of the patterns and structure of its genetic diversity. In this study, we assessed the levels and patterns of genetic variation in 71 populations along the whole distributional range of the WCC in the Iberian Peninsula. The two mitochondrial markers analyzed (Cytochrome Oxidase subunit I and 16S rRNA genes) indicated high levels of genetic diversity, which are significantly geographically structured in three main genetic groups, two corresponding to Northern and one to Central-Eastern and the westernmost Iberian Peninsula. The diversity found included new private haplotypes, and revealed the potential effect of paleogeographic barriers and last glaciations in the population structure observed. Current conservation and management programs for the WCC in the Iberian Peninsula should consider these three phylogeographic groups as essential management units in order to preserve the remaining genetic diversity in the species.